Radiographic, computed tomographic and magnetic resonance imaging appearances of primary V-cutting zone of resorption of lumbar vertebral body in Paget's disease - Jevtič, Vladimir (Radiology and oncology (Ljubljana), 2004)
Background. Paget's disease of bone typically demonstrates three evolutionary phases with the characteristic radiographic findings. The incipient stage is manifested by an advancing lytic zone of resorption. Unlike the skull and the long bones the primary advancing zone of rarefication has not been clearly demonstrated within the spine and pelvis. Case report. A 62-year-old man with histologically proved polyostotic Paget's disease was admitted to the hospitaldue to the exacerbation of pain at the toracolumbar junction with deterioration during the night. Due to slight elevation of acid phosphatase and clinical signs indicating prostatic hypertrophy the possibility of metastatic prostatic carcinoma has been raised. A bone scintigraphy with technetium phosphonate showed the expected marked increased uptake affecting numerous bones with the typical radiographic signs of Paget's disease. Besidesthese findings, there was also moderate focal accumulation within the right dorsal half of the vertebral body of L1. Conventional tomography, computed tomography (CT) and magnetic resonance imaging (MRI) demonstrated theprimary cutting zone of resorption affecting the same region. Conclusions. We present a unique case of Paget's disease with primary V-cutting zone withinthe undeformed vertebral body of L1 and spontaneous progression to the midphase of the disease on a three year follow-up.
Keywords: diagnostika; Magnetic Resonance Imaging; Magnetna resonanca slikovna; Middle Age; okostje; Osteitis Deformans; Pagetova bolezen; radiološka diagnostika; Spondiloliza; Spondylolysis; Srednja leta; Tomografija radiografska, računalniška; Tomography, X-Ray Computed